A novel humanized cutaneous lupus erythematosus mouse model mediated by IL-21-induced age-associated B cells. Issue 123 (September 2021) - Zhou, Suqing; Li, Qianwen; Zhou, Shengnan; Zhao, Ming; Lu, Liwei; Wu, Haijing; Lu, Qianjin
Abstract: Cutaneous lupus erythematosus (CLE) is a relapsing autoimmune disease, but key elements that drive disease initiation and progression remain elusive. To date, the lack of ideal murine model which resemble human cutaneous lupus makes it extremely challenging for moving mechanistic discoveries and novel therapeutics. Here, we prompt a humanized murine model to develop an inducible rapid-onset murine that performs cutaneous rather than systemic lupus, depending on the successful human immune system reconstruction from active lupus patients and UVB irradiation as for essentially pathogenic triggers. In addition, we demonstrate a newly discovered population of B cell with a unique phenotype, that of the age-associated B cell (ABC, T-bet + CD11b + ), exhibits B cell clusters in humanized cutaneous lupus. In the response of IL-21 and TLR7/9 signals, recruitment of autoreactive B cells to the position of inflammation with subsequent localized antibody production of IgG2a, IgG2b, IgG3, has the potential to exacerbate ongoing inflammation and thus driving lupus-like autoimmunity in a B-cell-dominant fashion. Overall, our model provides a relevant system for exploring the pathophysiology of cutaneous lupus, a suitable model for drug development, as well as updating a potential role of IL-21 and TLR7/9 to be targeted by biologics. Graphical abstract: The regulation network of ABC development and its pathogenic role in this newly established humanized CLE model. Firstly, we established a novel humanized CLE mouse model through the successfully engraftment of human PBMCs from active lupus patients. These mice performed lupus-like cutaneous lesions under suitable UVB irradiation. In addition, cutaneous lupus skin exhibited highly expressed human IL-21. These human-derived IL-21 cytokines play an important role in driving ABCs differentiation, including facilitating the expression of CD11b and transcription factor T-bet. On the other hand, apoptotic KCs induced by external UVB irradiation led an accumulation of endogenous nucleic acid. These nuclear autoantigens of CpG DNA and ssRNA can be recognized at the surface of B cells by the B cell receptor (BCR), and then these signals can trigger TLR7/9 in endosomes, further accelerating ABC development and proliferation, thereby prompting ABC clusters infiltration in skin lesion. These vigorous ABC responses were found to cause autoantibody production, including IgG2a, IgG2b, IgG3, but not IgG1. Antibody/antigen binding results in immune complexes that may work as positive stimulatory signals in autoimmunity, further highlighting the pathogenic role of ABC in tissue damage and ongoing inflammation. Image 1 Highlights: A novel humanized cutaneous lupus model for pathogenesis and medicine research. Aberrant distribution of IL-21 and age-associated B cells in this humanized model. Age-associated B cell differentiation and IgG secretion under IL-21 and TLR signals.